Correlation Between Serum C-Reactive Protein (CRP) and Soluble Cd40 Ligand (sCD40L) with Disease Activity by Modified Rodnan Skin Score (mRSS) in Systemic Sclerosis Patients in Indonesia - Widi Palupi Ayu Padmandani; Sumartini Dewi; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2018)
Introduction: Systemic Sclerosis (SSc) is a chronic autoimmune disease which presents immunological, endothelial dysfunction, skin and organs fibrosis. The inflammatory process is an important pathophysiology of systemic sclerosis. Disease activity assessment using clinical parameters of Modified Rodnan Skin Score (mRSS) changes and inflammatory laboratory parameters of C-Reactive Protein (CRP), Erytrocyte Sedimentation Rate (ESR) and soluble CD40 ligand. The European Scleroderma Study Group (EscSG) Activity Index uses CRP. CRP is higher sensitivity and specificity than ESR (80% and 91.2%). The study aims to evaluate the correlation between CRP and sCD40L with disease activity by mRSS.Methods: This research was a cross-sectional study, and data of mRSS and sCD40L were obtained from the study,